Como se resolve o sistema abaixo com o método de substituição
X+Y=7
X-Y=1 ?
Soluções para a tarefa
Respondido por
1
x+y=7
x-y=1
x+y=7
x=7-y
x-y=1
7-y-y=1
7-2y=1
-2y=1-7
-2y=-6
-y=-6/2
-y=-3 .(-1)
y=3
x+y=7
x+3=7 S={(4,3)}
x=7-3
x=4
x-y=1
x+y=7
x=7-y
x-y=1
7-y-y=1
7-2y=1
-2y=1-7
-2y=-6
-y=-6/2
-y=-3 .(-1)
y=3
x+y=7
x+3=7 S={(4,3)}
x=7-3
x=4
Usuário anônimo:
X+y=7---x=7-y .Vacilou.
Respondido por
1
.
![\left \{ {{x+y=7} \atop {x-y=1}} \right. \left \{ {{x+y=7} \atop {x-y=1}} \right.](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx%2By%3D7%7D+%5Catop+%7Bx-y%3D1%7D%7D+%5Cright.+)
substituição
isola x em
![x-y=1 \\ x=1+y x-y=1 \\ x=1+y](https://tex.z-dn.net/?f=x-y%3D1+%5C%5C+x%3D1%2By)
subst/ x em
![x+y=7 \\ 1+y+y=7 \\ 2y=7-1 \\ 2y=6 \\ y=6\div2 \\ y=3 x+y=7 \\ 1+y+y=7 \\ 2y=7-1 \\ 2y=6 \\ y=6\div2 \\ y=3](https://tex.z-dn.net/?f=x%2By%3D7+%5C%5C+1%2By%2By%3D7+%5C%5C+2y%3D7-1+%5C%5C+2y%3D6+%5C%5C+y%3D6%5Cdiv2+%5C%5C+y%3D3)
como
![x=1+y \\ x=1+3 \\ x=4 x=1+y \\ x=1+3 \\ x=4](https://tex.z-dn.net/?f=x%3D1%2By+%5C%5C+x%3D1%2B3+%5C%5C+x%3D4)
S={(4,3)}
substituição
isola x em
subst/ x em
como
S={(4,3)}
Perguntas interessantes
Matemática,
1 ano atrás
Inglês,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás